Pengaruh Manajemen Puskesmas dan Komitmen Kerja Petugas dengan Mutu Pengobatan di Poli Umum Puskesmas Cibinong, Cianjur - Sutrisno, Rahadian Nugi (Lembaga Yasin AlSys, 2024)
Community Health Center or puskesmas is one of the First Level Health Facilities (FKTP) that provides leading services in realizing the SPM in the Health Sector that has been determined by the government. The implementation of mainimal service standards (SPM) is closely related to the implementation of the National Health Insurance (JKN) and strengthens promotive and preventive actions in achieving a better degree of public health (Ministry of Health of the Republic of Indonesia. The purpose of this study is to determine the influence of puskesmas management and the commitment of officers to work with the quality of treatment at the Cibinong Public Poly Health Center, Cianjur. This research method uses a research design, structure and research strategy that is prepared so that researchers can get answers to the research problems studied. The research design used in the research on the Influence of Puskesmas Management and the Work Commitment of Officers with Quality Treatment at the Cibinong Public Poly Puskesmas, Cianjur is quantitative analytics with a cross sectional method using primary data. The results of this study show that there is a relationship between the commitment of officers' work with the quality of treatment at the Cibinong Public Health Center. Research conducted at Puskesmas Se-bangkalan and Puskesmas se-Karangasem showed results that are in line with this study. This is evidenced by a t-count of 5.417 and a free degree (n-k-1) or 43-2-1 = 40 obtained a t-table number of 2.201 so that t-count > t-table. Based on these provisions, it can be concluded that there is a significant influence between the implementation of puskesmas management on the quality of treatment.